(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
This study aims to explain the extent of the work ability of government officials in service to the community in the West Tahuna District Office in Sangihe Regency. This study uses qualitative research, with primary and secondary data sources, then the data obtained by interview, documentation and observation. The collected data is then analyzed through data reduction and data presentation then conclusions and verification are carried out so that they can provide answers to the research problem. The results of this study indicate that the ability of the apparatus to provide services to the community in the West Tahuna District of the Sangihe Islands Regency is evident from intellectual abilities and physical abilities. 1. The intellectual ability of the apparatus to provide services to the community is seen from their educational background, understanding of the rules, previous positions and support from leaders and colleagues. 2. The physical ability of the apparatus in providing services to the community is good because it is supported by the age factor of relatively young employees, the ability to take advantage of new technological work facilities as well as the existence of a good working relationship with the leadership and coworkers. And in order to improve the ability of officials in providing services to the community in the District of West Tahuna, Sangihe Regency, it is necessary to create an employee capacity development program in accordance with the existing work. And the nature and character as an apparatus that is responsive and cares for the needs of the community must be owned by every state civil apparatus.